Respuesta :

Answer:

x = -1, y = 1

Step-by-step explanation:

6 + 4x - 2y = 0 (1)

-3 - 7y = 10x (2)

From (1)

6 + 4x - 2y = 0 (1)

4x - 2y = -6 (3)

From (2)

-3 - 7y = 10x (2)

10x + 7y = -3 (4)

4x - 2y = -6 (3)

10x + 7y = -3 (4)

Using elimination method

Multiply (3) by 10 and (4) by 4 to eliminate x

40x - 20y = -60

40x + 28y = -12

28y - (-20y) = -12 - (-60)

28y + 20y = -12 + 60

48y = 48

y = 48/48

y = 1

Substitute y = 1 into (3)

4x - 2y = -6 (3)

4x - 2(1) = -6

4x - 2 = -6

4x = -6 + 2

4x = -4

x = -4/4

x = -1

x = -1, y = 1

The value of x in the equation is -1

ACCESS MORE